2021
DOI: 10.1071/wr20170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the use of drones to monitor a diverse crocodylian assemblage in West Africa

Abstract: Context West African crocodylian populations are declining and in need of conservation action. Surveys and other monitoring methods are critical components of crocodile conservation programs; however, surveys are often hindered by logistical, financial and detectability constraints. Increasingly used in wildlife monitoring programs, drones can enhance monitoring and conservation efficacy. Aims This study aimed to determine a standard drone crocodylian survey protocol and evaluate the drones as a tool to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…These outstanding perspectives brought by the fully automated, high resolution and multidimensional monitoring of ecological communities should not eclipse the potential negative effects of these technologies on wildlife. For example, unmanned and self‐navigating devices such as drones can affect animal physiology (Ditmer et al, 2015 ) and behaviour (Bennitt et al, 2019 ; Bevan et al, 2018 ; Mulero‐Pázmány et al, 2017 ; Schroeder et al, 2020 ), although these disturbances may be less detrimental than those caused by traditional survey methods, with less impact per unit of data (Aubert et al, 2022 ; Christiansen et al, 2016 ; Gallego & Sarasola, 2021 ) and some species becoming rapidly habituated to the presence of unmanned vehicles (Ditmer et al, 2019 ). Nevertheless, it is timely to (i) better quantify these impacts to avoid the generation of biased and unstandardised data; and (ii) aim to minimise these impacts to prevent animal stress.…”
Section: Combining Technologies To Fully Automate the Monitoring Of M...mentioning
confidence: 99%
“…These outstanding perspectives brought by the fully automated, high resolution and multidimensional monitoring of ecological communities should not eclipse the potential negative effects of these technologies on wildlife. For example, unmanned and self‐navigating devices such as drones can affect animal physiology (Ditmer et al, 2015 ) and behaviour (Bennitt et al, 2019 ; Bevan et al, 2018 ; Mulero‐Pázmány et al, 2017 ; Schroeder et al, 2020 ), although these disturbances may be less detrimental than those caused by traditional survey methods, with less impact per unit of data (Aubert et al, 2022 ; Christiansen et al, 2016 ; Gallego & Sarasola, 2021 ) and some species becoming rapidly habituated to the presence of unmanned vehicles (Ditmer et al, 2019 ). Nevertheless, it is timely to (i) better quantify these impacts to avoid the generation of biased and unstandardised data; and (ii) aim to minimise these impacts to prevent animal stress.…”
Section: Combining Technologies To Fully Automate the Monitoring Of M...mentioning
confidence: 99%
“…Many other studies have used drones to successfully count wildlife, from waterbirds to crocodiles (Aubert et al, 2021; Marchowski, 2021). Counting wildlife is an important facet of restoration ecology––for example, it can be part of measuring the composition, functionality and complexity of ecosystems prior to, during and following a restoration intervention.…”
Section: Restoration Planningmentioning
confidence: 99%
“…Drones can also be less disturbing to wildlife (if species‐specific protocols are followed) (Aubert et al, 2021; Gallego & Sarasola, 2021) and cover larger spatial extents than traditional field surveys. If protocols are not followed, drones can be detrimental to wildlife.…”
Section: Restoration Planningmentioning
confidence: 99%
“…Featuring studies from both aquatic and terrestrial ecosystems, this special issue of Wildlife Research highlights the environmental and taxonomic reach of drone research today for observing wildlife and, as a corollary, the myriad ways in which drones are helping overcome limitations of and complement more traditional sampling approaches. For example, Aubert et al (2022) reported a pioneering drone survey of a West African crocodilian assemblage. They found that although they were less effective than nocturnal visual (on-the-ground) surveys, drone surveys were better at detecting crocodilians than were diurnal visual surveys, in large part because their aerial perspective overcomes on-the-ground visual obstructions caused by plants and other forms of habitat complexity.…”
mentioning
confidence: 99%
“…Moreover, drones alleviated many of the considerable logistical constraints imposed by both traditional techniques. This marked efficiency advantage is critical in the system studied by Aubert et al (2022), and many others, where focal taxa are simultaneously imperilled and difficult to monitor. Sudholz et al (2022) pushed a different research boundary, showing that drone surveys are an effective means of monitoring invasive species, in their case Rusa deer (Rusa timorensis) in Queensland, Australia, particularly when paired with automated detection via machine learning.…”
mentioning
confidence: 99%